IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. BANK RAKYAT INDONESIA TBK. KANTOR UNIT PORONG - AYU TITOFIANTI, NANDA Ayu (Jurnal Akuntansi AKUNESA, 2012)
This study aims to describe the implementation of corporate social responsibility (CSR) PT. BRI Unit Porong. This type of study is a qualitative descriptive study. Implementation of CSR by BRI Unit Porong focusing on Community Development Program of BRI Peduli Pasar Rakyat (PESAT) carried out in Porong Market, as well as the Partnership Program activities in the form of loan disbursement Partnership. Kata Kunci: CSR, Program Bina Lingkungan, Program Kemitraan